Starting Point for Protocols on the Use of Hyperdiluted Calcium Hydroxylapatite (Radiesse®) for Optimizing Age-Related Biostimulation and Rejuvenation of Face, Neck, Décolletage and Hands: A Case Series Report - Massidda E (Dove Medical Press, 2023)
Enrico Massidda1,2 1Private Practice in Aesthetic Medicine, Milano, Cagliari, Italy; 2Member of Società Internazionale di Medicina Estetica, Rome, ItalyCorrespondence: Enrico Massidda, Email drenricomassidda@gmail.comAbstract: Radiesse® is a dermal filler made of calcium hydroxylapatite, a natural component of the human body, which, in diluted and hyperdiluted forms, promotes, unlike other fillers, neocollagenesis, neoelastinogenesis, fibroblast proliferation, and angiogenesis, leading to a long-term improved skin quality, elasticity, tightening, and firmness. This case series examined the use of Radiesse® (Merz, Frankfurt, Germany) for skin rejuvenation and regeneration through a long-lasting action of collagen biostimulation. The report explored for the first time the use of different dilution ratios of Radiesse® in 50 patients of varying ages and skin needs. By combining microboluses, tunneling, and/or fanning techniques, Radiesse® was superficially injected in different body regions, including the full-face, neck, décolletage, and hands. The treatment was effective in improving skin thickness, laxity, and wrinkles in 95% of 30- 40 year-olds, 80% of 40- 60 year-olds, and 70% of > 60 year-olds, with an average improvement of 81.6% for the general population. The treatment was well-tolerated with no significant adverse effects reported. The report also describes specific cases and includes pictures comparing the baseline condition to the changes obtained after different months and Radiesse® sessions. The patients reported a clear improvement in skin firmness and brightness, as well as a visible improvement in wrinkles' appearance. This report found that diluting and hyperdiluting Radiesse® with flexible dilution ratios favoured a treatment's individualization, providing improved skin quality, elasticity, tightening, and firmness, without volume augmentation. In conclusion, it highlights the versatility and flexibility of Radiesse® and emphasizes its efficacy and safety in skin rejuvenation and regeneration.Keywords: aesthetics, biostimulation, calcium hydroxylapatite, hyperdilution, Radiesse, skin rejuvenation